Pendataan Warga Baru Perumahan Ciptaland untuk Pengurusan Surat Pindah - Kho, Ferry; Saputra, Antoni; Veronica, Veronica; Afnesia, Utari; Dikjayasa, Parisatria; Panjaitan, Denti Masti; Safitri, Tasrika Nur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
Citizens are a group of people who stay in a certain place or region that is recorded in the area by the chief of citizens responsible for that region. At this time, recording of new resident?s data has not been carried out properly because there are some citizens who are lazy to report to their chief and some citizens suddenly move to other places without permission or prior intimation to their chief. Due to this, some residents find it difficult to make a new letter of residency. The purpose of this activity to help new residents in making a new letter of residency. Our implementation method of this activity is to study the location Perumahan Ciptaland, interview the residents of Perumahan Ciptaland with a group discussion, followed by a literature study, and collect the resident?s data. This activity of Sephora is very helpful to the new residents of Perumahan Ciptaland for making a new letter of residency and also to help the chief of residents to collect new data on the new residents. This activity had a positive effect on Ciptaland residents; they no longer feel difficult again to make a new letter of residency with their chief.